2018 IEEE Energy Conversion Congress and Exposition (ECCE) 2018
DOI: 10.1109/ecce.2018.8557402
|View full text |Cite
|
Sign up to set email alerts
|

Safe-Operating-Area of Snubberless Series Connected Silicon and SiC power devices

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The secondary mechanism can be due to the limitation of the material, such as reaching intrinsic temperature, or due to a significant leakage through the gate dielectric. It can also occur when the parasitic bipolar junction transistor (BJT) latches [2]- [7]. Furthermore, in Si IGBTs, it has been demonstrated that filamentation may occur, where the filament will be pinned to field crowding areas of the parasitic BJTs [8].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary mechanism can be due to the limitation of the material, such as reaching intrinsic temperature, or due to a significant leakage through the gate dielectric. It can also occur when the parasitic bipolar junction transistor (BJT) latches [2]- [7]. Furthermore, in Si IGBTs, it has been demonstrated that filamentation may occur, where the filament will be pinned to field crowding areas of the parasitic BJTs [8].…”
Section: Introductionmentioning
confidence: 99%